2021
DOI: 10.1136/gutjnl-2020-322874
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and 3D imaging of a novel ΔNp63-expressing basal cell type in human pancreatic ducts with implications in disease

Abstract: ObjectiveThe aggressive basal-like molecular subtype of pancreatic ductal adenocarcinoma (PDAC) harbours a ΔNp63 (p40) gene expression signature reminiscent of a basal cell type. Distinct from other epithelia with basal tumours, ΔNp63+ basal cells reportedly do not exist in the normal pancreas.DesignWe evaluated ΔNp63 expression in human pancreas, chronic pancreatitis (CP) and PDAC. We further studied in depth the non-cancerous tissue and developed a three-dimensional (3D) imaging protocol (FLIP-IT, Fluorescen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 60 publications
1
17
0
Order By: Relevance
“…In keeping with this observation, the MC2 methylation subtype described by Espinet and others ( Espinet et al, 2021 ) and aligning with the transcriptomic basal-like subtype is suggested to derive from ductal cells. Furthermore, a recent manuscript demonstrating the presence of a rare ΔNp63 + ductal cell population in the normal human pancreas raises the possibility that these might represent a cell of origin for tumours with basal-like/squamous features ( Martens et al, 2021 ). Moreover, cell reprogramming, as a driver of basal-like/squamous PDAC, might have a cell-dependent context.…”
Section: Molecular Determinants Of Cell Lineages In Pdacmentioning
confidence: 99%
“…In keeping with this observation, the MC2 methylation subtype described by Espinet and others ( Espinet et al, 2021 ) and aligning with the transcriptomic basal-like subtype is suggested to derive from ductal cells. Furthermore, a recent manuscript demonstrating the presence of a rare ΔNp63 + ductal cell population in the normal human pancreas raises the possibility that these might represent a cell of origin for tumours with basal-like/squamous features ( Martens et al, 2021 ). Moreover, cell reprogramming, as a driver of basal-like/squamous PDAC, might have a cell-dependent context.…”
Section: Molecular Determinants Of Cell Lineages In Pdacmentioning
confidence: 99%
“…PDA derived from acinar cells is associated with PanIN lesions, both before and after progression to invasive carcinoma, while duct-derived carcinomas display far fewer attendant PanIN lesions [13] . Importantly, duct-derived carcinoma cells show a tendency towards basal-like gene expression, while acinar-derived tumors more closely resemble the classical subtype identified in human cohorts [29] . Definitively ascribing a cell of origin to advanced human malignancies is impossible, meaning the role of the cell of origin in human PDA subtypes will remain undetermined.…”
Section: Determinants Of Transcriptional Subtypesmentioning
confidence: 73%
“…Then, the brains were dehydrated in increasing concentrations of 1propanol pH 9 (1-propanol in CUBIC-R+; 25, 50, 75, 2 x 100 %, 30 min each step, and a final overnight step at 100 %). The next day, dehydrated samples were incubated in increasing concentrations of ethyl cinnamate (ECi, #112372, Sigma-Aldrich, Germany; ECi in 1-propanol pH 9; 25, 50, 75, 2 x 100 %, 45 min each step) [53][54][55] and were kept in 100 % ECi until image acquisition in a Light-sheet Fluorescence Microscope (LSFM).…”
Section: Refractive Index Matching With Ethyl Cinnamatementioning
confidence: 99%
“…CUBIC-L induced limited swelling, which was minimized further during the first RI matching step with CUBIC-R+(M) 50,51 . After dehydration with pH-adjusted 1-propanol series, a last step using the organic solvent ECi was performed, taking advantage of the complementary RI matching effect of both CUBIC-R and ECi 54 . The combination of 1-propanol pH 9 and ECi preserved endogenous fluorescence [53][54][55] .…”
Section: Neuroanatomical Characterization Of Zsgreen1-expressing Cell...mentioning
confidence: 99%